Students’ Attitude Towards English Language Learning - Herwiana, S; Laili, E N (Journal of Educational Method and Technology, 2019)
This study is try to find out the students’ attitude towards English language learning in Jombang elementary schools. Attitude is one of the factors that influence the language acquisition. The study used qualitative research methodology. The data were gathered by using questionnaire. The findings showed that most of the students have positive attitude towards English. But, there is a finding that showed the students’ competence in learning English is poor. Positive attitude did not influence their competence in acquiring English. Some suggestions for government to make a guide or curriculum of English teaching –learning in elementary school. So that the teachers know how to teach English for young learner appropriately.